2003
DOI: 10.3201/eid0908.030069
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in Finland, 1995–1999

Abstract: We analyzed laboratory-based surveillance candidemia data from the National Infectious Disease Register in Finland and reviewed cases of candidemia from one tertiary-care hospital from 1995 to 1999. A total of 479 candidemia cases were reported to the Register. The annual incidence rose from 1.7 per 100,000 population in 1995 to 2.2 in 1999. Species other than Candida albicans accounted for 30% of cases without change in the proportion. A total of 79 cases of candidemia were identified at the hospital; the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
96
8
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 43 publications
15
96
8
9
Order By: Relevance
“…Sandven et al reported a low and rather constant annual rate of candidemia in Norway from 1991 to 1999 (2.2% of BSI or 2.17 per 100,000 people), whereas Poikonen et al reported annual rates to increase in Finland from 1.7 to 2.2 per 100,000 people from 1995 to 1999 (18,20,21). In this context, our estimated annual rate of 11 per 100,000 people seems very high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sandven et al reported a low and rather constant annual rate of candidemia in Norway from 1991 to 1999 (2.2% of BSI or 2.17 per 100,000 people), whereas Poikonen et al reported annual rates to increase in Finland from 1.7 to 2.2 per 100,000 people from 1995 to 1999 (18,20,21). In this context, our estimated annual rate of 11 per 100,000 people seems very high.…”
Section: Discussionmentioning
confidence: 99%
“…tribution rather unchanged during the last decade, whereas in Finland, an increase was observed from 1995 to 1999 (18,20,21). There are few data on the epidemiology of fungemia in Denmark.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies from abroad have noted increases in the incidence of hospitalization with candidemia that were similar in magnitude to the increase in our study. 8 Our analysis has multiple limitations. It relied on ICD-9-CM coding to identify candidemia-related hospitalizations, which may have predisposed our case ascertainment to misclassification.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that considerably higher incidences for candidaemia have been reported from US, 7,13 where candidaemia is much more common in hospitalised patients when compared to the situation in Finland. 15,16 In the present series, C. albicans was clearly dominating, probably due to lack of fluconazole prophylaxis. This finding is in a striking contrast with the series reported by Safdar et al 7 where non-albicans strains (C. glabrata, C. krusei, C. parapsilosis) were the causative agents; all patients had received fluconazole prophylaxis.…”
Section: Discussionmentioning
confidence: 88%